Metaphor in Petatah Petitih of Babako Ceremony in Minangkabau Wedding Tradition - Fauziah Khairani Lubis; Syamsul Bahri; Aulia Risky Harlina (RIRAI Publisher, 2024)
ABSTRACT Metaphore is used in Petatah Petitih of Minangkabau wedding tradition, Babako ceremony, usually functions to beautify the language in conveying an advice and the values of life. The tradition of Babako in Minangkabau is a way to preserve the local wisdom , Minangkabau culture and its language. The objective of this study is to explore more about Metaphore in Minangkabau wedding traditions, especially in the Babako ceremony. This research uses a qualitative approach with a focus on text analysis from Petatah Petitih, a form of oral literature used in Minangkabau traditional ceremonies. Data was obtained through participant observation and interviews with traditional leaders and ceremony participants. The kinds of Metaphore are found in Petatah Petitih of Babako ceremony are Ontological Metaphore (Personification) 36,1%, structural metaphore 27,7%, Ontological Metaphore (Metonymy) 19,4%, Oriental Metaphore 16,6%. Ontological Metaphore (personification) 36,1% is a highest one, it shows the language used describing several objects that exist in nature moving with natural influences such as imitating human movements. This adds beauty to the language used. It describes the nature and human are as two components strongly constructing the civilization, tradition and language development of Minangkabau in society. The results of the analysis show that metaphore are used creatively in Petatah Petitih of Babako ceremony to convey life values, social norms and moral messages in the context of Minangkabau marriages.